Ethnicity and the performance of identity - Budiman, Manneke (UI Scholars Hub, 2011)
This essay looks into the novels of two Indonesian women writers, Perempuan Kembang Jepun (Lan Fang 2009) and Dimsum terakhir (Clara Ng 2006), which depict the struggles of the major female characters in negotiating their